2011
DOI: 10.4103/0970-9290.93474
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of association between periodontitis and PLBW among selected population of practising gynecologists in Andhra Pradesh

Abstract: There is a need for interdisciplinary approach for the prevention of PLBW cases by the integration of periodontal care into obstetric management. Effort should be made to increase awareness among the gynecologists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Overall, the level of knowledge in the present survey reflected gynecologists’ familiarity with various pregnancy-related oral health topics, which is in accordance with previous studies. [ 13 14 15 16 ] Although the overall knowledge level of the gynecologists was satisfactory in this study, however, there still exist minor misconceptions amongst gynecologists regarding provision of dental treatments during pregnancy. This is of importance to the dentists as it acts as a barrier for them in providing the most appropriate treatment to their pregnant patients.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Overall, the level of knowledge in the present survey reflected gynecologists’ familiarity with various pregnancy-related oral health topics, which is in accordance with previous studies. [ 13 14 15 16 ] Although the overall knowledge level of the gynecologists was satisfactory in this study, however, there still exist minor misconceptions amongst gynecologists regarding provision of dental treatments during pregnancy. This is of importance to the dentists as it acts as a barrier for them in providing the most appropriate treatment to their pregnant patients.…”
Section: Discussionmentioning
confidence: 82%
“…Meanwhile, systematic data to evaluate the knowledge, awareness, and opinions of gynecologists regarding oral health care during pregnancy and the effect of maternal oral health on the pregnancy outcomes are very limited. [ 11 12 13 14 15 16 17 18 ] To our knowledge, no study has been published that assessed the extent of healthcare providers’ knowledge regarding the association between oral health and pregnancy outcomes in the UAE. The aim of this study was to evaluate the knowledge, awareness, and opinions of gynecologists regarding oral health care during pregnancy in the UAE.…”
Section: Introductionmentioning
confidence: 99%
“…In a study done by Nutalapatiet. only 38.3% of gynecologists were aware that periodontal diseases can affect the outcome of delivery 33 . In our study, only 23.6% of individuals were aware about the relationship between periodontitis and preterm low birth weight deliveries.…”
Section: Discussionmentioning
confidence: 99%
“…This result is lower than that reported in other studies[ 17 19 23 24 ] and higher than that reported by some other studies. [ 20 25 ]…”
Section: Discussionmentioning
confidence: 99%